Moderate presbycusis boosts audio-visual integration, but not lip-reading - Delmas, Tanguy; Pham Van Cang, Mathieu; Gerenton, Grégory; Lefeuvre, Jérôme; Doelling, Keith B.; Arnal, Luc H.; Lazard, Diane S. (Hearing research, 2025)
•Visual speech comprehension (lip-reading) declines with age.•Visual speech comprehension does not increase with moderate hearing loss.•Audio-visual integration increases with moderate hearing loss.•Hearing loss may impose different plastic pressure depending on its severity. In audiological practice, speech comprehension is typically assessed in the auditory modality alone (speech in quiet or noise). However, in real-life communication when the auditory input is degraded - due to noise or hearing loss (HL) - individuals rely on ancillary signals to enhance speech perception. Audio-visual (AV) integration is particularly effective in improving speech perception in noisy environments, yet the influence of HL and aging on this ability remains underexplored. This study aims to disentangle the effects of HL and age on visual aspects of speech processing, both unimodally (lip-reading) and bimodally (AV integration). In sixty-five participants aged 50 and older, with hearing abilities ranging from normal to moderate HL (from 4 to 63 dB HL), we tested speech comprehension in challenging auditory, visual (lip-reading) and AV conditions using an adaptive procedure. AV gain (AV performance minus Auditory-alone performance) served as a measure of audio-visual integration. Using multiple linear regressions and causal inference to account for the relative impact and potential interactions between HL and age, our results show that mild to moderate HL does not improve unimodal visual processing but does improve AV gain. In contrast, aging negatively impacts visual speech processing but does not directly affect AV gain. These findings suggest that mild to moderate HL enhances the integration of visual and auditory speech cues to improve AV performance without affecting the efficacy of the visual information processing itself, while age-related decline in visual speech processing does not appear to effect overall AV integration. We propose that this reflects a form of central plasticity, in which moderate HL drives adaptive changes at high-order multimodal levels, counterbalancing age-related sensory decline in visual speech processing to maintain AV speech integration. Future research should explore how this plasticity evolves with more severe HL.